2016
DOI: 10.1016/j.ssci.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational complexity and organizational accident risk: A literature review

Abstract: Due to increased outsourcing in many industries, organizations are becoming larger and more interorganizationally complex and numerous operations now require cooperation among employees from different organizations. This paper presents a review of empirical literature addressing safety issues in complex interorganizational systems wherein the potential for major organizational accidents is present. Thematic analysis of the literature resulted in four main themes: economic pressures, disorganization, dilution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 33 publications
3
49
0
2
Order By: Relevance
“…Subcontractors are often part of the most hazardous operations. The indicators in this paper support some of the safety challenges found in previous research about the use of subcontractors [11]. For example, the Safe Job Analysis (SJA) may be viewed as a counter measure of disorganization and confusion of roles and responsibilities.…”
Section: Framework and Safety Indicatorssupporting
confidence: 68%
See 1 more Smart Citation
“…Subcontractors are often part of the most hazardous operations. The indicators in this paper support some of the safety challenges found in previous research about the use of subcontractors [11]. For example, the Safe Job Analysis (SJA) may be viewed as a counter measure of disorganization and confusion of roles and responsibilities.…”
Section: Framework and Safety Indicatorssupporting
confidence: 68%
“…A concern with this development is how to ensure safety in operations with the increasing use of subcontractors. Milch and Laumann [11] reviewed inter-organizational complexity with regards to accident risk and found that four main themes are treated in research: economic pressures, disorganization, a dilution of competence, and organizational differences. The study found that inter-organizational complexity can hinder efficient safety management and thus elevate the risk.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, such details are relevant in order for the reader to evaluate the work. Interview guides were developed based on previous findings from review of the literature on interorganizational complexity and safety (Milch and Laumann 2016). Additionally, since our point of departure concerned organizational safety and major accidents, the theoretical perspectives of Reason (1997) and HRO Sutcliffe 2007, 2015;Weick et al 2008) were also used as a source of inspiration in developing questions.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent paper, Milch and Laumann (2016) reviewed extant empirical literature addressing interorganizational safety issues in safety-critical industries. Safety issues identified were found to stem from economic pressures among companies, problems with organizing and coordinating operational activity across organizational interfaces, lack of competence and experience in personnel, and organizational differences between companies.…”
Section: Comparing Findings With Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation